PENGEMBANGAN SISTEM INFORMASI AGRIBISNIS DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Utomo Putra,M. R. Yantu, Sulaeman, Edi (AGROTEKBIS, 2015)
This aims of this study is develop agribusiness information systems of Labuan Toposo Village specifically the sub system process (farming). This research conducted in Labuan Toposo Village on January to February 2015. Data used were primary data and secondary data. Primary data were taken by purposive method. There were 14 respondents to be reviewed. Analyze method that used in this researah are Quantitative Description, Flowchart and GIS analysis. The results showed there are 272 farmers registered in the 11 active farmer groups with total ownership of agricultural land 214.87 Ha and plantation 39.53 Ha. Most agricultural commodities grown are Chili, Corn, Cocoa, Coconut, Paddy,and Tomato. Land use consists of 60.58% for protected forest area, 23.46% for the people and the forest plantation area, 8.78% for Protected Area, 6.87% for agricultural land, and 0.31% for residential area and activity place. This study also resulted in agribusiness information system in the form of database applications for farmer groups and their members, and data agricultural commodities and websites that can display agricultural information of Labuan Toposo Village.